"Lack of concentration" : a clinical investigation among school children - Jowell, Ruth (Department of Psychology, 2016)
The problem arose in the setting of the Child Guidance Clinic of the University of Cape Town where children were from time to time referred for "Lack of Concentration". It soon became evident that "lack of concentration" was an extremely vague, descriptive term used to cover a variety of conditions. The parent and teacher were able to state that the child could not concentrate, but they had little knowledge of what was actually lacking in the child. The Clinic did not have at its disposal: (1) a precise measuring instrument for assessing the child's level of concentration; (2) a definite training programme in which the child could participate; (3) methods of assessing the main factors associated with lack of concentration. As a result only rather general advice could be given to parents whose children were referred for this problem. Thus, it was obvious that, despite the importance of this problem particularly in the field of education, there was little real understanding of it, and research in this very extensive field seemed to be indeed opportune. The main purpose of the present study is to arrive at a clearer understanding of the term 'Lack of Concentration' for the clinical psychologist. This implies : (1) defining concentration and accounting for its lack in the group of children studied; (2) showing the inter-relationships and links between concentration and other variables; (3) a) devising tests of concentration b) formulating a training procedure with the object of developing concentration c) devising a set of alternate tests to assess the effectiveness of tbe training programme; (4) evaluating the present status of the problem and emphasizing the need for further research and investigation.